2008
DOI: 10.2353/ajpath.2008.061249
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Delivery of T-box21 Small Interfering RNA Ameliorates Autoimmune Alopecia (Alopecia Areata) in a C3H/HeJ Mouse Model

Abstract: Autoimmune alopecia (alopecia areata) is considered to be triggered by a collapse of immune privilege in hair follicles. Here we confirmed that infiltrating CD4 T lymphocytes around hair follicles of patients with alopecia areata were primarily CCR5-positive with few CCR4-positive cells, suggesting a dominant role of Th1 cells in the alopecic lesion. Given this finding, we sought to elucidate the effect of cytokine therapy in C3H/HeJ mice, a mouse model of alopecia areata, by applying recombinant interleukin-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 23 publications
3
47
0
Order By: Relevance
“…Possibly, the recent reports of the use of T-box21 small interfering RNA ameliorating alopecia areata in mouse models [50 ] will lead in that direction. Regardless, more controlled studies need to be performed in adults and children with alopecia areata, with particular focus on the patients' measures of quality of life.…”
Section: Other Treatmentsmentioning
confidence: 97%
“…Possibly, the recent reports of the use of T-box21 small interfering RNA ameliorating alopecia areata in mouse models [50 ] will lead in that direction. Regardless, more controlled studies need to be performed in adults and children with alopecia areata, with particular focus on the patients' measures of quality of life.…”
Section: Other Treatmentsmentioning
confidence: 97%
“…For example, Nakamura et al indicated the Th1-predominant lymphocytic infi ltration around hair follicles of patients with alopecia areata [18]. In another study, Ito et al demonstrated that patients with acute AA have a higher frequency of circulating CXCR3+ CD4+ Th1 cells [19].…”
Section: Discussionmentioning
confidence: 99%
“…Their results indicate that 90% of wild-type mice [IFN-γ(+/+)] developed AA, after grafting alopecia areata-affected skin, while none of the IFN-γ(-/-) mice exhibited hair loss [26]. Moreover, it has been reported that local injections of both IL-4 and neutralizing anti-IFN-γ antibody effectively treated alopecia in C3H/ HeJ mice [27].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, topical application of cationic nanoliposomes loaded with specific siRNA has been tested as an effective approach for control of cutaneous melanomas [146], and siRNAs conjugated to cationized gelatin showed a positive effect on symptoms of alopecia in C3H/HeJ mice [147]. A promising line of research has been developed by Kerner and colleagues that proposes modulating androgen receptor expression with RNAi for hair and skin therapy [148,149].…”
Section: Treatments Of Hair Growth Disorders: Room For Improvementmentioning
confidence: 99%